PENGARUH BIAYA TENAGA KERJA, BIAYA PEMASARAN DAN VOLUME PENJUALAN TERHADAP LABA BERSIH PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI TAHUN 2020-2024 - Riska Diva Pertiwi; Hadi Samanto; Maya Widyana Dewi (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
This study aims to determine the impact of labor costs, marketing costs, and sales volume on the net profit of manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) for the years 2020-2024. This research utilizes a descriptive research type with a quantitative approach. The population of this study includes manufacturing companies in the food and beverage sub-sector that are listed on the IDX for the years 2020-2024, totaling 48 companies. The sampling technique employed is purposive sampling, involving 20 companies. The data source for this research utilizes secondary data. Data collection methods are obtained from the Indonesian Stock Exchange (IDX). This study employs data analysis methods, which include descriptive statistical tests, classical assumption tests, and hypothesis testing, comprising multiple linear regression analysis, F test, t test, and the coefficient of determination (R2) test.The results of this study indicate that labor costs do not have a significant effect, while marketing costs and sales volume do have a significant effect.